Borrowing constraints and consumption behavior in Japan - Midori Wakabayashi; Charles Yuji Horioka (Osaka University, Institute of Social and Economic Research (ISER), 2005)
In this paper, we use Japanese micro data to examine what characteristics borrowing-constrained households have and whether borrowing constraints have an important influence on household consumption behavior. We identify borrowing-constrained households using three different indicators, some of which are unique to our data source, and find that the characteristics of households that are likely to be borrowing-constrained differ depending on which of the three indicators we use. We also find that changes in current income have a positive and significant impact on changes in consumption in the case of households that are likely to be borrowing-constrained but not in the case of households that are unlikely to be borrowing-constrained. This result suggests that borrowing constraints have an important influence on household consumption behavior and that the presence of borrowing constraints is one explanation for why the life cycle-permanent income hypothesis does not hold in the real world.
Keywords: 330; Verbraucherkredit; Kreditwürdigkeit; Konsumentenverhalten; Lebenszyklus; Einkommenshypothese; Japan; Theorie-Praxis-Verhältnis